Trends in Clinical Research Including Asian American, Native Hawaiian, and Pacific Islander Participants Funded by the US National Institutes of Health, 1992 to 2018 - Ðoàn, Lan N; Takata, Yumie; Sakuma, Kari-Lyn K; Irvin, Veronica L (JAMA Network Open, 2019)
IMPORTANCE: Advancing the health equity agenda for Asian American, Native Hawaiian, and Pacific Islander (AA/NHPI) individuals has become an intersecting priority for federal agencies. However, the impact of federal investments and legislation to ensure systematic processes and resources to eliminate health disparities in AA/NHPI populations is unclear. OBJECTIVE: To perform a portfolio review of clinical research funded by the National Institutes of Health (NIH) for AA/NHPI populations and determine the level of NIH investment in serving these populations. DESIGN, SETTING, AND PARTICIPANTS: Cross-sectional study in which the NIH Research Portfolio Online Reporting Tools Expenditures and Results system was queried for extramural AA/NHPI-focused clinical research projects conducted in the United States from January 1, 1992, to December 31, 2018. Clinical research funded under research project grants, centers, cooperative awards, research career awards, training grants, and fellowships was included, with an advanced text search for AA/NHPI countries and cultures of origin. Project titles and terms were screened for inclusion and project abstracts were reviewed to verify eligibility. Descriptive analyses were completed. MAIN OUTCOMES AND MEASURES: Outcomes included NIH funding trends and characteristics of funded projects and organizations. The proportions of AA/NHPI-related funding trends were calculated using 2 denominators, total NIH expenditures and clinical research expenditures. RESULTS: There were 5460 records identified, of which 891 studies were reviewed for eligibility. Of these, 529 clinical research studies focused on AA/NHPI participants composed 0.17% of the total NIH budget over 26 years. Projects studying AA/NHPI individuals in addition to other populations were funded across 17 NIH institutes and centers. The top 5 funders collectively contributed almost 60% of the total funding dollars for AA/NHPI projects and were the National Cancer Institute ($231 584 664), National Institute on Aging ($108 365 124), National Heart, Lung, and Blood Institute ($67 232 910), National Institute on Minority Health and Health Disparities ($62 982 901), and National Institute on Mental Health ($60 072 779). Funding of these projects ($775 536 121) made up 0.17% of the overall NIH expenditures ($451 284 075 000) between 1992 and 2018, and 0.18% ($677 479 468) of the NIH research budget after 2000. Funding for AA/NHPI projects significantly increased over time, but the proportion of the total NIH budget has only increased from 0.12% before 2000 to 0.18% after 2000. Of total funding, 60.8% was awarded to research project grants compared with only 5.1% allocated to research career awards, training grants, and fellowships. CONCLUSIONS AND RELEVANCE: Increases in research dollars for AA/NHPI clinical research were not associated with increases in the overall NIH research budget, and underrepresentation of AA/NHPI subgroups still remains. Without overt direction from federal entities and dedicated funds for health disparities research, as well as parallel efforts to increase diversity in the biomedical workforce, investments may continue to languish for AA/NHPI populations.